PARADIGMA ZIARAH DALAM PENAFSIRAN ALKITAB - Demianus Nataniel (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2018)
One of the critical problems in hermeneutic praxis is the tendency of emphasizing one part in a hermeneutical circle, namely context, text, or reader. Therefore we should take into account the whole part in an interdependence balance. Instead of emphasizing one of the part in the hermeneutic circle, this paper offers pilgrimage as a paradigm in interpreting the Bible so that the whole part in a hermeneutical circle can be put in an interdependence balance. The use of pilgrimage as a paradigm in the interpretation of the Bible should be understood as Groome has been doing by taking pilgrimage as a paradigm in his Shared Christian Praxis approach.